Sosialisasi Pentingnya SOP dalam Mewujudkan Efisiensi, Transparansi, dan Akuntabilitas di Desa Pasir Putih: Peran Papan Informasi dalam Pengelolaan Dana Desa - Irmania Rambu Nggiri; Kristina Trisnawati Lusi; Yohanes Alesanro Mario; Mariano Yoseph Sanga Blikololong; Margareta Novianti Ya; Yohanes Kornelius Ethelbert (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service project aims to socialize the importance of implementing Standard Operating Procedures (SOP) to enhance efficiency, transparency, and accountability in the management of Village Funds in Pasir Putih Village, Nagawutung District. Using an information board as a communication medium, village officials, the Village Consultative Body (BPD), and the community were involved participatively in the planning and implementation of the socialization process. As a result, the activity successfully increased public understanding and awareness of the importance of information transparency in the management of Village Funds, while also encouraging transparent behavior from village officials. The participatory approach proved effective in fostering more transparent and accountable village governance.